Factorial design approach for optimization of floating microspheres of diltiazem hydrochloride - Panwar, Mr. Mangal Singh (Asian Journal of Pharmaceutics (AJP), 2015)
The aim of this study was to perform optimization of floating microspheres of diltiazem hydrochloride for the prolongation of gastric residence time. The microspheres were prepared by a nonaqueous solvent evaporation method using polycarbonate. A full factorial design was applied to optimize the formulation. Preliminary studies revealed that the concentration of polymer and stirring speed significantly affected the characteristics of floating microspheres.The optimum batch of microsphere exhibited smooth surfaces with good flow and packing properties, prolonged sustained drug release, remained buoyant for more than 10 h, high entrapment efficiency up to 97% w/w. Scanning electron microscopy confirmed the hollow structure with particle size in the order of 190 μm. The studies revealed that the increase in concentration of polycarbonate increased the drug release from the floating microspheres.The results of two third full factorial design revealed that the concentration of polycarbonate (X1) and stirring speed (X2) significantly affected drug entrapment efficiency, percentage release. Key words: Diltiazem hydrochloride, factorial design, floating microspheres, polycarbonate